Analysis of Service Quality and Customer Satisfaction at Spice Beach Club Lovina - Arisanti, Ni Putu Hertina; Trianasari; Widiastini, Ni Made Ary (Politeknik Negeri Bali, 2024)
This research is a descriptive qualitative study that aims to analyse service quality and customer satisfaction, especially at Spice Beach Club Lovina. The discussion of the research leads to an explanation related to factors that are important in service quality and customer satisfaction as well as the strategies used by Spice Beach Club to maintain service quality and customer satisfaction. This research was conducted for four months with data collection methods, namely observation, interviews, and documentation. The interview in this research were conducted with one person operational manager, one person restaurant manager and two employees of Spice Beach Club and using 50 guest comment card samples to determine guest reviews on service quality. The results of this research show that employees and facilities owned by Spice Beach Club are strategies used to maintain service quality and customer satisfaction as well as friendliness, politeness, always responsive to guests, provide assurance to the guests, and reliable employees are important factors in service quality.